Seven years of teenage pregnancy in an inner London genitourinary medicine service – a retrospective cohort study. (December 2014) - Hegazi, Aseel; Daley, Natalie; Williams, Elizabeth; McLeod, Felicity; Rafiezadeh, Saba; Prime, Katia
Summary: Young people attending genitourinary medicine services are at high risk of unplanned pregnancy. We performed a retrospective cohort study to identify characteristics of pregnant teenagers accessing an inner London genitourinary medicine service. There were 481 pregnancies in 458 teenagers with 54 previous pregnancies and 46 previous terminations of pregnancy. The under-18 and under-16 teenage pregnancy rates were 92.1 and 85.8 per 1000 age-matched clinic attendees, respectively. Median age was 17.1 years. 'Black Other' teenagers ('Black British', 'Mixed White-Black Caribbean' and 'Mixed White-Black African') were over-represented, compared to our clinic population, while those of White ethnicity were under-represented. Few pregnancies (1.5%) were planned with the majority (64%) intending terminations of pregnancy. Most teenagers did not use consistent contraception. Two-thirds of patients had attended genitourinary medicine services in the past and sexually transmitted infection prevalence at presentation was high. Effectively targeting the sexual and reproductive health needs of teenage genitourinary medicine clinic attendees may have a significant impact on reducing sexually transmitted infections, unplanned pregnancy and terminations of pregnancy in this group.